The Role of Liver Biopsy in the Management of Patients with Liver Disease - Florence Wong (Canadian Journal of Gastroenterology)
The role of liver biopsy in the diagnosis and management of liver disease is a controversial issue even among hepatologists. Although most causes of elevated liver enzymes can be determined, or at least suspected, on the basis of a careful history and laboratory tests, histological assessment remains the gold standard for most liver diseases. Histological evaluation can either confirm or refute clinical diagnoses and can provide information about the severity and stage of disease. Occasionally, the liver biopsy also provides an additional diagnosis. The spectrum of nonalcoholic fatty liver disease accounts for a substantial proportion of cases of chronically elevated liver enzymes and can be reliably diagnosed only by liver biopsy. Prognostic information can be obtained in patients with this disorder, as well as in those with alcoholic liver disease and viral hepatitis, and liver biopsy can be used as a guide to their management.